2018
DOI: 10.1111/acer.13823
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Alcohol Use on Frontal White Matter in HIV

Abstract: This study provides evidence of HIV-related associations between alcohol use and indicators of axonal integrity loss along the ATR, a frontal pathway involved in the inhibition of addictive or unwanted behaviors. Reduced axonal integrity of this pathway was greatest in HIV+ participants with an AUD, even when considering the effect of age-adjusted disease length and severity (nadir CD4). This finding implicates a potential biological mechanism linking reduced integrity of frontal white matter to the high preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 69 publications
4
9
0
Order By: Relevance
“…These findings are also consistent with MRS studies that reported significant Age*HIV interactive effects, particularly for frontal WM metabolites (Cysique et al, 2013;Ernst & Chang, 2004;Harezlak et al, 2011); Age*HIV interactive effects were also reported in subcortical regions (Kuhn et al, 2018). Together, these findings both support and expand upon prior literature demonstrating jointly deleterious effects of HIV and aging on WM microstructure (Gullett et al, 2018;Holt et al, 2012;Nir et al, 2014;Towgood et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These findings are also consistent with MRS studies that reported significant Age*HIV interactive effects, particularly for frontal WM metabolites (Cysique et al, 2013;Ernst & Chang, 2004;Harezlak et al, 2011); Age*HIV interactive effects were also reported in subcortical regions (Kuhn et al, 2018). Together, these findings both support and expand upon prior literature demonstrating jointly deleterious effects of HIV and aging on WM microstructure (Gullett et al, 2018;Holt et al, 2012;Nir et al, 2014;Towgood et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, as expected and consistent with a larger literature (e.g., (Chang et al, 2011;Filippi, Ulu g, Ryan, Ferrando & van Gorp, 2001;Pomara et al, 2001;Seider et al, 2016;Wang et al, 2011;Wright, Heaps, Shimony, Thomas & Ances, 2012)), a significant main effect of HIV was found on WM. However, some TOIs evidenced WM deterioration that was greater in the seronegative control group, which may be explained by frontal and temporal lobes, consistent with knowledge of a relatively heterogeneous yet typically predominantly frontal-subcortical involvement in HIV (Ettenhofer & Abeles, 2009;Gullett et al, 2018;Heaton et al, 2010;Hinkin, Castellon, Atkinson, & Goodkin, 2001;Price, Bartlett, & Bloom, 2016;Valcour et al, 2004a;Valcour, Sithinamsuwan, Letendre, & Ances, 2011). These findings are also consistent with MRS studies that reported significant Age*HIV interactive effects, particularly for frontal WM metabolites (Cysique et al, 2013;Ernst & Chang, 2004;Harezlak et al, 2011); Age*HIV interactive effects were also reported in subcortical regions (Kuhn et al, 2018).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…(Marquine et al, 2016). Neuroimaging studies suggest that alcohol use disorder (AUD) co-occurring with HIV may exacerbate certain structural brain abnormalities which can affect cognitive functioning (Lewis-de Los Angeles et al, 2017, Bladowska et al, 2013, Sullivan et al, 2011, Rosenbloom et al, 2010, Nelson et al, 2005, Pfefferbaum et al, 2005, Chang et al, 2004, Pfefferbaum et al, 2002, Durazzo et al, 2007, Cardenas et al, 2005, Meyerhoff et al, 1995, Pfefferbaum et al, 2007) (Gullett et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol use disorder (AUD) among PLWH is estimated to be 2 to 4 times higher than among the general population (Duko et al, 2019; Galvan et al, 2002; Petry, 1999; Vagenas et al, 2015). AUD in PLWH adversely affects brain structural, functional, and metabolic functions, as well as cognition (Cohen et al, 2019; Gullett et al, 2018; Meyerhoff, 2001; Míguez‐Burbano et al, 2014) and therefore may be a major contributor to cognitive deficit among PLWH.…”
mentioning
confidence: 99%